Salmonella isolates in the introduced Asian house gecko (Hemidactylus frenatus) with emphasis on Salmonella weltevreden, in two regions in Costa Rica - Porras, Laura (2015)
The Asian house gecko Hemidactylus frenatus has been widely introduced in Costa Rica and tends to establish in human settlements. Some studies in other invaded countries have suggested that this gecko plays a significant role in the epidemiology of salmonellosis and it is of value to public health. To our knowledge, no studies have examined Salmonella from this species in Costa Rica. Therefore, we collected 115 geckos from houses in two Costa Rican regions. We examined gut contents for Salmonella through microbiological analysis. Presumptive Salmonella spp. were sent to a reference laboratory for serotyping and antimicrobial susceptibility testing. Molecular typing was also conducted with the main Salmonella isolates of zoonotic relevance in Costa Rica. H. frenatus was found in 95% of the houses surveyed. Salmonella was isolated in 4.3% of the samples, and four zoonotic serovars were detected. None of the isolates were resistant to the antibiotics most frequently used for salmonellosis treatment in Costa Rica. All Salmonella isolates from the lower out of H. frenatus are associated with human salmonellosis. Pulsotypes from Salmonella enterica serotype Weltevreden were identical to the only clone previously reported from human samples in Costa Rica. Molecular typing of Salmonella Weltevreden suggested that H. frenatus harbors a serovar of public health importance in Costa Rica. Results demonstrated that H. frenatus plays a role in the epidemiology of human salmonellosis in two regions of Costa Rica. However, more detailed epidemiological studies are needed to understand better the role of the Asian house gecko with human salmonellosis, especially caused by Salmonella Weltevreden, and to quantify its risk in Costa Rica accurately